NOKTAH HITAM AGAMA DALAM CERPEN MADAM BAPTISTE (SUATU TINJAUAN SOSIOLOGI SASTRA) - Waluyo, Sukarjo (HUMANIKA, 2012)
Using literature sociology approach, The Short Story of Madame Baptiste by Guy de Maupassant is found as an interesting literary work for its telling about how religion serve the society problems. Because of the religious, religion is often regarded doing discrimination in serving society needs. The religionists often got accusation, finally. Keywords: sociology, religion, discrimination, religionist